Food insecurity and the Sistema Unico de Assistência Social (SUAS): reflections on the “Plano Brasil sem Fome” - Santos de Campos, Eliane Christine; Marques, Rosa Maria (Textos & Contextos (Porto Alegre), 2024)
This article aims to problematize the involvement of the Sistema Único de Assistência Social in the implementation of the “Plano Brasil sem Fome”, a strategy built by the current federal government to confront poverty and extreme poverty through actions to combat hunger. This is a bibliographic review and documentary research, having as a guiding the “Plano Brasil Sem Fome”. Two aspects stand out for the fulfilment of the responsibilities of the SUAS in the execution of the Plan: financing, involving the federative pact and the recompos;ition and qualification of workers in the municipalities, the main operators of the SUAS.